Pattern of Nailfold Capillaroscopy in Patients With Systemic Lupus Erythematosus - Ting ZHAO,; Fu-an LIN,; Hong-pu CHEN, (Archives of Rheumatology, 2020)
Objectives: This study aims to assess the nailfold capillary changes in patients with systemic lupus erythematosus (SLE), particularly among those with Raynaud’s phenomenon (RP), and the correlation between nailfold capillary changes and autoantibodies and disease activity. Patients and methods: A total of 85 patients (9 males, 76 females; median age 31 years; range, 15 to 58 years) with newly diagnosed SLE were selected between July 2016 and July 2018 from our hospital. Disease activity was scored by the SLE Disease Activity Index. Nailfold capillaroscopy (NFC) was performed in all patients. Results: Normal pattern, non-specific pattern, and scleroderma pattern were found in 13 (15.3%), 64 (75.3%), and eight (9.4%) patients, respectively. There was no significant difference between anti-double stranded deoxyribonucleic acid, anti-Smith antibodies, and low complements (all p>0.05), while significant differences of NFC pattern were found between low disease activity and high disease activity (p=0.002). RP was present in 31.7% of SLE patients, and the NFC findings in SLE patients with and without RP were significantly different in dilatation (81.5% vs. 14.0%). Conclusion: The results of our study showed that capillary changes were very common in patients with SLE, which seem to associate with disease activity and RP condition.